Personality disorders and pathological gambling in adolescents and young people with addiction to slot machines - Espinoza, Luis S. (2018)
The object of this study was to explore the relationship between patterns of maladaptive personality and pathological gambling in a group of gamblers addicted to slot machines. The sample consisted of 120 male and female subjects divided into two groups: a group of 60 pathological gamblers aged 18 to 24 who attended the Pathological Gambling Recovery Program at the Instituto de Psicología Integral del Perú (IPIP), and a group of 60 non-gamblers aged 18 to 24 who were psychology students of a private university in Lima. Data was obtained using the Millon Clinical Multiaxial Inventory II (MCMI-II), the Pathological Gambling Brief Questionnaire (PGBQ), and the Structured Clinical Interview for Pathological Gambling (SCI-PG). The results showed that 81,7 % of the pathological gamblers addicted to slot machines had at least one personality disorder, in comparison with the other group which yielded 40%. The most prevalent personality disorder was the self-defeating disorder, followed by the passive-aggressive, narcissistic and borderline disorders. Moreover, there are significant differences in maladaptive personality patterns between gamblers and non-gamblers according to Millon’s theory.